CTG - Roberta Calegari; Mirco Musolesi; Franco Raimondi; Cecilia Mascolo (Proceedings of the the 6th joint meeting of the European software engineering conference and the ACM SIGSOFT symposium on The foundations of software engineering, 2007)
Multitarget stool DNA (mt-sDNA) is a sensitive stool-based test for colorectal cancer (CRC) screening. Limited referral-center data suggest low rates of incident aerodigestive cancers after a positive mt-sDNA and negative colonoscopy; community-based outcomes are unknown. Retrospective cohort study of adults referred for colonoscopy after positive mt-sDNA in a large community practice (2017-2021). Among patients with negative colonoscopy, we manually recorded post-colonoscopy recommendations, findings if additional colonoscopies had been performed, aerodigestive cancer diagnosis, and last clinical follow-up. Observed cancer incidence was compared with Surveillance, Epidemiology, and End Results (SEER) data. Of 1,176 patients completing colonoscopy after positive mt-sDNA, 328 (28%) had negative findings. Median cohort age was 67 (IQR 59-72) years. Colonoscopy was performed at a median of 53 days after mt-sDNA sample collection. Post-colonoscopy recommendations aligned with multi-society task force (MSTF) guidelines in 59% of patients. Thirty-two patients underwent repeat colonoscopy with a median of 3.5 (1.9-4.4) years later; 2 (6.3%) had advanced serrated lesions, and no CRC was detected. Median clinical follow-up was 4.4 (3.4-5.6) years. Seven patients developed aerodigestive cancers (2 pancreatic, 5 lung), consistent with expected age- and sex-adjusted SEER incidence (n=7.62) (p=0.823). In this community cohort, when a positive mt-sDNA was followed by negative colonoscopy, rates of subsequent advanced colorectal neoplasia and aerodigestive cancer were low. Most patients received recommendations for subsequent colonoscopy that were consistent with MSTF guidelines. Findings further support the current MSTF recommendation of no additional evaluation for extra-colonic malignancy in asymptomatic patients after high quality follow-up colonoscopy.